The rise of the global company : Multinationals and the making of the modern world - Fitzgerald, Robert, 1959- (Cambridge : Cambridge University Press, 2015)
"This is the first full account of how an influential form of commercial organization - the multinational enterprise - drove globalization and contributed to the making of the modern world. Robert Fitzgerald explores the major role of multinational enterprises in the events of world history, from the nineteenth century to the present, revealing how the growth of businesses that operated across borders contributed to an unprecedented worldwide transformation and deepening interdependence between countries. He demonstrates how international businesses shaped the economic development and competitiveness of nations, their politics and sovereignty, and the balance of power in international relations. The Rise of the Global Company uses the lessons of history to question prominent contemporary interpretations of multinationals and their consequences, and offers a truly wide-ranging survey of multinational enterprise, spanning two hundred years and five continents"--
Machine generated contents note: 1. Multinationals, states and the international economy; 2. Empires of business: 1870-1914; 3. The reverse gear?: 1914-48; 4. Cold War and the new international economic order: 1948-80; 5. Global economics?: 1980-2012; Conclusion: international business in time; Tables; References; Bibliography; Index.
Includes bibliographical references and index.
Keywords: International business enterprises; BUSINESS & ECONOMICS / Economic History